2021
DOI: 10.1016/j.heliyon.2021.e07721
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity evaluation for volatiles and water extract of commercialized star anise

Abstract: Background Usually, it takes about a year since the harvested fresh star anise fruit (SAF) reaches the market for consumer usage, all this time with different handling processes and different storage circumstances greatly affect its quality as well as its chemical composition and biological activity. Aim This study investigated the chemical constituents for volatiles and water extracts of commercialized SAF, as well as, their bioactivities. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Additionally, the highest content of the other chemical compounds and the best quality of the essential oil was achieved after SFE. In another investigation by Sabry et al [14], the content of trans-anethole obtained by the hydrodistillation (HD) method was smaller (47.16%) in comparison to the SFE used by Wang et al [13].…”
Section: Chemical Characteristicsmentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, the highest content of the other chemical compounds and the best quality of the essential oil was achieved after SFE. In another investigation by Sabry et al [14], the content of trans-anethole obtained by the hydrodistillation (HD) method was smaller (47.16%) in comparison to the SFE used by Wang et al [13].…”
Section: Chemical Characteristicsmentioning
confidence: 92%
“…Sabry et al [14] evaluated the antibacterial activities of I. verum volatile-oil extract and water extract against four bacterial strains: Escherichia coli, Bacillus cereus, Salmonella typhi and S. aureus. It was revealed that the volatile-oil extract showed stronger antibacterial activity than the water extract (MIC = 6.6-10.0 µL SAF/mL and MIC = 16.4-29.6 µL SAF/mL, respectively).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Besides, extracts of plants showed a valuable capacity for toxigenic fungal growth (assessed in synthetic media) [14,15]. The promising impacts of wild plants like stevia, Opuntia Ficus indica [16,17], and star anise [18] were recorded. Also, extracted seed oils showed a significant ability to inhibit mycotoxin production by their toxigenic fungi strains, among which were jojoba, jatropha [19], black cumin seed [20], pomegranate oil [21], and hibiscus oils [22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is a large category of harmful microorganisms known as toxigenic fungi. These fungi possess the capacity to produce chemical substances recognized as mycotoxins [ 12 , 13 ]. These toxins are secondary metabolites secreted by fungi, and as highly dangerous compounds they act as a hidden enemy threat concerning crop production, as well as, animals and public health.…”
Section: Introductionmentioning
confidence: 99%
“…The application of plant extracts as a rich source of bioactive molecules in the growth media of fungi could affect their metabolic pathways [ 13 ]. These changes decrease the harmful impact of fungal contamination due to the absence or by limiting the existence of secondary metabolites [ 19 ].…”
Section: Introductionmentioning
confidence: 99%